Nurcholis Majid's Study of Thought for the Civilization of Science: A Critical Reflection on the Basic Values of Struggle in the Context of Islam and Indonesianness - Khoirul Amri Rambe; Siti Fatimah (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2026)
Nurcholish Madjid (Cak Nur) is a central figure in the renewal of Indonesian Islamic thought whose legacy continues to be a vital reference in contemporary national discourse. This paper aims to critically analyze Nurcholish Madjid's intellectual project in his quest to build a